OPTIMASI ADSORPSI Cr(VI) PADA SILIKA GEL DARI ABU SEKAM PADI TERMODIFIKASI DIFENILKARBAZIDA (Si-DPZida) - Henny Puspa Dewi Giri; I Wayan Sudiarta; Ida Ayu Raka Astiti Asih (Jurnal Kimia (Journal of Chemistry), 2014)
Adsorption of chromium (VI) on silica gel modified by diphenilcarbazide (Si-DPZida) have been studied. Parameters analyzed were surface acidity by acid-base titration method, specific surface area by absorption of methylene blue method, optimum conditions of adsorption (pH, contact time), and isotherm adsorption. The results showed that Si-DPZida adsorbent has surface acidity (Kal) of 1,5996 mmol/g with the number of active sites of 9,6328 x 1020 atom/g with specific surface area of 4.4538 m2/g. The optimum adsorption process of chromium (VI) by both Si-DPZida occurred at pH 5  and 15 minutes of contact time.  The isotherm adsorptions on both adsorbents tend to follow Freundlich adsorption pattern.